Regulating Light‐Sensitive Gate of Organic Photoelectrochemical Transistor toward Sensitive Biodetection at Zero Gate Bias. Issue 11 (19th August 2021) - Lu, Meng-Jiao; Chen, Feng-Zao; Hu, Jin; Zhou, Hong; Chen, Guangxu; Yu, Xiao-Dong; Ban, Rui; Lin, Peng; Zhao, Wei-Wei
Abstract : Although great advances have been achieved in the field of organic electrochemical transistor (OECT) biodetection, its fundamental sensing principles are still highly limited. Different from current dominating protocols for OECT biodetection, herein, the bio‐dependent regulation of light‐sensitive gate electrode for transducing the corresponding biological events is introduced. Exemplified by the enzymatically catalytic growth of gold nanoclusters to gold nanoparticles on the 3D TiO2 /carbon fiber matrix gate electrode, the photoelectrochemistry of the hybrid gate photoanode shifts from the type‐II heterojunction to plasmonic type, rendering reduced photon‐to‐electron efficiency and thus decreased current response of the gate photoanode. By connecting to an alkaline phosphatase‐associated sandwich immunoassay event toward the representative analyte of C‐reactive protein, the model system exhibits target‐dependent tunability and good analytical performance at zero gate bias. A new sensing principle for OECT biodetection is manifested, and would spur more creativity to explore the rich light–matter interplay for advanced OECT biodetection. Abstract : Biologically modulating light‐sensitive photoanode of organic electrochemical transistor is achieved by biocatalytic growth of Au nanoclusters to Au nanoparticles on a TiO2 substrate, shifting the gate photoelectrochemistry from the type‐II heterojunction to plasmonic type. In the detection of C‐reactive protein antigen, the as‐proposed OECT biosensor exhibits good performance at zero gate bias.